EFFECT OF EXPERIENTIAL MARKETING IN BUILDING BRAND EQUITY: A CASE OF SELECTED UNILEVER TANZANIA BRANDS - Mukiira, Evelyn Maradufu; Musau, Mr. Celestine; Munyao, Mr. Joseph (International Journal of Supply Chain Management, 2017)
Purpose: To analyze the effects of experiential marketing in building brand equity for selected brands of Unilever Tanzania. Methodology: The study adopted an explanatory and descriptive research design. Findings: The study found that experiential marketing is the best way to market a product, and senses are heightened when they experience the product/brand firsthand. The study found that experiential marketing practices have a positive effect on consumers and overall brand equity. The study also found that it is a challenge in capturing marketing insights, connecting with customers, building strong brands, shaping the market offerings, delivering and communicating value, creating long-term growth, and developing marketing strategies while building brand equity. Unique contribution to theory, practice and policy: Potential benefits of such a study include raising marketers' awareness of the importance of brand equity needs of the FMCG companies by making use of experiential marketing as an avenue to meeting the targets and achieving high returns for each of their brands. This research will benefit Unilever Tanzania and other FMCG companies, as it will provide a roadmap that they can use to market their product/brands better. The research will play a great role in assisting mangers by exploring how they can more effectively ensure that the brands curve out a bigger share of the market by tapping into unutilized opportunities. This insight into the significant role played by experiential marketing could also be used to steer other brands that are looking for value to use this channel of marketing campaigns.